2010
DOI: 10.1590/s0001-37652010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of the ichthyofauna associated with seagrass beds ( Halodule wrightii) in Formoso River estuary - Pernambuco, Brazil

Abstract: Seagrass beds are used by juvenile fishes in different ways, generally as nursery sites, shelter from predators, reducing competition and increasing availability of food resources, thus establishing a relationship of connectivity with other ecosystems. In the present study, the community structure of the ichthyofauna associated with seagrass beds on the Formoso River (Pernambuco -Brazil) was evaluated during the winter of 2008. Twenty-seven manual trawls (15 daytime and 12 nighttime) were performed, and a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
1
21
0
5
Order By: Relevance
“…In this case, the group of fish is the most dominant carnivores on seagrass beds in the study areas. Similarly, the group of fish carnivores contributed about 70% of the total fish abundance in seagrass beds at Donghsa Island's (Lee et al, 2014), but there was differences, the group of fish carnivores (20%) and herbivores (20%) in the Formoso River estuaryPernambuco, Brazil (Pereira et al, 2010). Besides that, (Appendix 6) showed that seagrass provides a diversity of fish food on seagrass in the study area.…”
Section: The Abundance and Diversity Of Fish As Indicators Of Seagrasmentioning
confidence: 86%
See 1 more Smart Citation
“…In this case, the group of fish is the most dominant carnivores on seagrass beds in the study areas. Similarly, the group of fish carnivores contributed about 70% of the total fish abundance in seagrass beds at Donghsa Island's (Lee et al, 2014), but there was differences, the group of fish carnivores (20%) and herbivores (20%) in the Formoso River estuaryPernambuco, Brazil (Pereira et al, 2010). Besides that, (Appendix 6) showed that seagrass provides a diversity of fish food on seagrass in the study area.…”
Section: The Abundance and Diversity Of Fish As Indicators Of Seagrasmentioning
confidence: 86%
“…The diversity index value of fish found in the study area is relatively equal to the index value diversity of fish with two locations of seagrass beds. The location of seagrass beds both are in Sikao Bay, Trang Province, Thailand with the value of the Shannon-Wiener index (H') = 2.7 (Phinrub et al, 2015) and, in Formoso River Estuary-Pernambuco, Brazil (H') = 2.66 (Pereira et al, 2010). Nevertheless, have considerable differences with the value of fish diversity on seagrass beds in the Jordanian coast of the Gulf of Aqaba (H') = 1.4 (Khalaf et al, 2012).…”
Section: The Abundance and Diversity Of Fish As Indicators Of Seagrasmentioning
confidence: 99%
“…Em cada estuário, foram selecionadas três estações com características semelhantes: a) Prado de fanerógama -formado por Halodule wrightii, conhecido como capim-agulha (Pereira et al, 2010;Silva, 2011); b) Manguezal -área formada por mangue composto principalmente por Rhyzophora mangle (Braga et al, 1989); e c) Recife -recifes com formação arenítica, dispostos em paralelo à linha de costa. Em Suape, foi escolhido um ponto adicional denominado Estaleiro, que corresponde a uma antiga área de mangue, totalmente desmatada e modificada pela construção do estaleiro e ampliação do porto, e sujeita ao fluxo parcialmente interrompido do rio Tatuoca, devido à construção de uma ponte/barragem (Figura 1) (Tabela 1).…”
Section: Amostragemunclassified
“…Deste modo, uma maior densidade de larvas de peixes durante o período noturno é uma característica comum nas assembleias ictioplanctônicas em diferentes ambientes (Ré, 1999), tendo sido registrada em estudos pretéritos realizados na área de estudo (Pereira et al, 2010;Silva-Falcão, 2012;Silva-Falcão et al, 2013). Esta característica também foi observada nos ambientes estudados, indicando que o padrão é mantido mesmo em áreas sujeitas a diferentes impactos ambientais.…”
Section: Ictioplânctonunclassified
“…To provide more empirical data on the community structure of the ichthyofauna that makes use of seagrass beds, Pedro Pereira and colleagues of the Departamento de Oceanografia of the Universidade Federal de Pernambuco have investigated the Formoso River estuary situated in the Municipality of Tamandaré at the Pernambuco State. The study area is placed at the limits of two environmental protection areas -Guadalupe and Costa dos Corais (Pereira et al 2010). With daytime and nighttime manual trawls An Acad Bras Cienc (2010) 82 (3)…”
mentioning
confidence: 99%